Anatomy of the long head of biceps femoris: An ultrasound study. Issue 6 (13th June 2016) - Tosovic, D.; Muirhead, J.C.; Brown, J.M.M.; Woodley, S.J.
Abstract : Hamstring strains, particularly involving the long head of biceps femoris (BFlh) at the proximal musculotendinous junction (MTJ), are commonly experienced by athletes. With the use of diagnostic ultrasound increasing, an in‐depth knowledge of normal ultrasonographic anatomy is fundamental to better understanding hamstring strain. The aim of this study was to describe the architecture of BFlh, using ultrasonography, in young men and cadaver specimens. BFlh morphology was examined in 19 healthy male participants (mean age 21.6 years) using ultrasound. Muscle, tendon and MTJ lengths were recorded and architectural parameters assessed at four standardised points along the muscle. Measurement accuracy was validated by ultrasound and dissection of BFlh in six male cadaver lower limbs (mean age 76 years). Intra‐rater reliability of architectural parameters was examined for repeat scans, image analysis and dissection measurements. Distally the BFlh muscle had significantly ( P < 0.05) shorter fascicles and larger pennation angles than proximal sites. Agreement between ultrasound and dissection (cadaver study) was excellent for all architectural parameters, except pennation angle (PA), and MTJ length. All other measures demonstrated good‐excellent repeatability. BFlh is not uniform in architecture when imaged using ultrasound. It is likely that its distal‐most segment is better suited for force production in comparison to the more proximal segments, which show excursive potential, traits which possibly contribute to the high rate of injury at the proximal MTJ. The data presented in this study provide specific knowledge of the normal ultrasonographic anatomy of BFlh, which should be of assistance in analysing BFlh injury via imaging. Clin. Anat. 29:738–745, 2016. © 2016 Wiley Periodicals, Inc.